Characteristics of catfish oil, red palm oil and shark liver oil as functional foods - Ulil Amri; Andarini Diharmi; Mery Sukmiwati (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Functional food is a food ingredient in addition to basic needs as nutrients that can also play a functional role in health. This research aimed to determine the physicochemical characteristics and fatty acid composition of catfish oil, red palm oil, and shark liver oil as functional food ingredients. The research method was to extract fish oil from belly flap, purify catfish oil, and process red palm oil (RPO) from crude palm oil (CPO). The analysis parameters consisted of sensory analysis, oil chemical characteristics (free fatty acid analysis, peroxide, iodine, saponification, and acid numbers), total carotene, tocopherol, and analysis of fatty acid composition. The results showed that the catfish oil after being purified had sensory characteristics, smelled slightly fishy and semi-solid, and had a bright yellow color. The results of the analysis of chemical characteristics showed that the free fatty acid numbers of catfish oil and shark liver oil were following IFOS standards (1.33 and 0.62%), and the RPO numbers for peroxide and free fatty acids according to the SNI standards (9.56 meq kg and 1.44%). The highest ω-3 and ω- 6 fatty acids were in shark liver oil (3.56 and 35.35%), followed by catfish oil (1.72 and 19.9%). and RPO does not contain ω-3 and ω-6. Catfish oil, RPO, and shark liver oil act as functional foods. The fatty acid composition of catfish, shark liver and red palm oil contains saturated and the fatty acid composition of catfish, shark liver and red palm oil contains saturated and unsaturated fatty acids. Mono and poly unsaturated fatty acid (FUFA anf MUFA) in crude catfish oil, pure catfish oil, shark liver oil, and red palm oils were 56.71, 58.12, 63.81 and 47.39% respectively. The result of analysis showed composition of in catfish oil 1.72 and 19.9 %. The content of and of shark liver oil was 3.5 and 35.5%. Whereas in red palm oil does not Ω 3 and Ω 6. The content of EPA and DHA in shark liver oil was 0.08, 0.09 but not in catfish and red palm oil. The total content of carotene and tocopherol in red palm oil was 513.86 and 925.80 mg/kg, respectively. The nutritional composition of catfish oil, red palm oil, and shark liver oil has the potential to be used as functional food. Keywords:Characteristic physicochemicalCaroteneTocopherolω-3ω-6